Web-based versus in-person methods for training lay community health advisors to implement health promotion workshops: participant outcomes from a cluster-randomized trial. Issue 4 (28th June 2018) - Holt, Cheryl L; Tagai, Erin K; Santos, Sherie Lou Zara; Scheirer, Mary Ann; Bowie, Janice; Haider, Muhiuddin; Slade, Jimmie
Abstract : Lay persons trained either in-person or online are able to deliver effective cancer awareness and education in their communities, which can help increase cancer screening. Abstract: Project HEAL ( Health through Early Awareness and Learning ) is an implementation trial that compared two methods of training lay peer community health advisors (CHAs)—in-person ("Traditional") versus web-based ("Technology")—to conduct a series of three evidence-based cancer educational workshops in African American churches. This analysis reports on participant outcomes from Project HEAL. Fifteen churches were randomized to the two CHA training methods and the intervention impact was examined over 24 months. This study was conducted in Prince George's County, MD, and enrolled 375 church members age 40–75. Participants reported on knowledge and screening behaviors for breast, prostate, and colorectal cancer. Overall, cancer knowledge in all areas increased during the study period ( p < .001). There were significant increases in digital rectal exam ( p < .05), fecal occult blood test ( p < .001), and colonoscopy ( p < .01) at 24 months; however, this did not differ by study group. Mammography maintenance (56% overall) was evidenced by women reporting multiple mammograms within the study period. Participants attending all three workshops were more likely to report a fecal occult blood test or colonoscopy at 24 months ( p < .05) than those who attended only one. These findings suggest that lay individuals can receive web-based training to successfully implement an evidence-based health promotion intervention that results in participant-level outcomes comparable with (a) people trained using the traditional classroom method and (b) previous efficacy trials. Findings have implications for resources and use of technology to increase widespread dissemination of evidence-based health promotion interventions through training lay persons in community settings.